COMPARATIVE ANALYSIS OF COMPOSITE WORDS - Radjabova Lyubov Usmanovna (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
An article on complex words and their comparative analysis. Complex words are words that consist of at least two stems that occur as free forms in the language. In a compound word, the direct components are given integrity and structural coherence that make them function as a separate lexical unit in a sentence.